2015
DOI: 10.1016/j.jde.2015.08.052
|View full text |Cite
|
Sign up to set email alerts
|

Moore–Gibson–Thompson equation with memory, part II: General decay of energy

Abstract: Abstract. We study a temporally third order (Moore-Gibson-Thompson) equation with a memory term. Previously it is known that, in noncritical regime, the global solutions exist and the energy functionals decay to zero. More precisely, it is known that the energy has exponential decay if the memory kernel decays exponentially. The current work is a generalization of the previous one (Part I) in that it allows the memory kernel to be more general and shows that the energy decays the same way as the memory kernel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
100
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 141 publications
(101 citation statements)
references
References 21 publications
1
100
0
Order By: Relevance
“…We also mention the recent paper [15] where the authors consider (1.16) with a memory damping term and show an exponential decay of the energy provided that the kernel is exponentially decaying. This result is generalized in [16], where it is shown that the memory kernel decay determines the solution decay.…”
Section: Introduction Derivation Of the Model And Well-posednessmentioning
confidence: 83%
“…We also mention the recent paper [15] where the authors consider (1.16) with a memory damping term and show an exponential decay of the energy provided that the kernel is exponentially decaying. This result is generalized in [16], where it is shown that the memory kernel decay determines the solution decay.…”
Section: Introduction Derivation Of the Model And Well-posednessmentioning
confidence: 83%
“…This restriction can actually be removed; but to get energy bound, we need to impose condition on g(0). see [22]. Item 3 implies the exponential decay of the kernel.…”
Section: Mainmentioning
confidence: 99%
“…Roughly speaking, the memory term creates damping by weakening the total energy in the first place: it borrows energy to initialize the deformation and pays back in the long run. We exploit this point in another paper [22].…”
Section: Introductionmentioning
confidence: 97%
“…See in this regard the works by Kaltenbacher, Lasiecka, and Marchand, Marchand, McDevitt, and Triggiani, and Kaltenbacher, Lasiecka, and Pospieszalska . Later on, Irena Lasiecka and Xiaojun Wang showed a general decay result for the MGT equation with memory.…”
Section: Introductionmentioning
confidence: 94%
“…We obtain a system of differential equations of four orders with respect to the variable t with constant coefficients and the initial conditions (11); consequently, we get a Cauchy problem of linear differential equations with smooth coefficients that is uniquely solvable. Thus for every N there exists a function u N (x) satisfying (6).…”
Section: Solvability Of the Problemmentioning
confidence: 99%